COMPARISON OF FREEWAY SPACE DISTANCE OF WILLIS METHOD WITH DIGITAL PHOTO ANALYSIS METHOD IN BANJAR TRIBE - Fachriani Fachriani; Rahmad Arifin; Dewi Puspitasari; Diana Wibowo; I Wayan Arya Krishnawan Firdaus (Dentino: Jurnal Kedokteran Gigi, 2024)
Background: The face's vertical dimension or vertical height is the distance between two anatomical points, namely the points on the maxilla and mandible. In measuring the vertical dimension, vertical dimensions of rest (DVR) and vertical dimensions of occlusion (DVO) must be measured. The difference between the vertical dimension of rest (DVR) and the vertical dimension of occlusion (DVO) is called the freeway space (FWS) or interocclusal distance. Freeway space is a key requirement for optimal comfort and function of a partial or complete denture. Each individual's freeway space distance is the movement of muscle function, which can be measured by direct methods such as the Willis method using calipers and the digital photo analysis method using computer software. Two measurement methods can be used to measure freeway space distance direct and indirect. Purpose: To analyze the difference between freeway space distance measured by the Willis method and by digital photo analysis of Adobe Photoshop and Corel Draw graphic design software in the Banjar tribe (a review of students at the Faculty of Dentistry, Universitas Lambung Mangkurat Banjarmasin). Methods: This study is a quantitative study with an analytic observational method and a cross-sectional approach. This study was conducted by collecting data simultaneously at one time by comparing three different methods on the same sample without being given any treatment. Results: One Way ANOVA test is 0.296 (P>0.05) which means there is no significant difference. Conclusion: There is no significant difference between the results of measuring freeway space distance using the Willis method with a digital caliper and digital photo analysis with Adobe Photoshop and Corel Draw software.